Wolbachia-Based Dengue Virus Inhibition Is Not Tissue-Specific in Aedes aegypti - Amuzu, Hilaria E. (PLoS Negl Trop Dis, 2016)
BACKGROUND: Dengue fever, caused by the dengue virus (DENV), is now the most common arbovirus transmitted disease globally. One novel approach to control DENV is to use the endosymbiotic bacterium, Wolbachia pipientis, to limit DENV replication inside the primary mosquito vector, Aedes aegypti. Wolbachia that is naturally present in a range of insects reduces the capacity for viruses, bacteria, parasites and fungi to replicate inside insects. Wolbachia’s mode of action is not well understood but may involve components of immune activation or competition with pathogens for limited host resources. The strength of Wolbachia-based anti DENV effects appear to correlate with bacterial density in the whole insect and in cell culture. Here we aimed to determine whether particular tissues, especially those with high Wolbachia densities or immune activity, play a greater role in mediating the anti DENV effect. METHODOLOGY/FINDINGS: Ae. aegypti mosquito lines with and without Wolbachia (Wildtype) were orally fed DENV 3 and their viral loads subsequently measured over two time points post infection in the midgut, head, salivary glands, Malpighian tubules, fat body and carcass. We did not find correlations between Wolbachia densities and DENV loads in any tissue, nor with DENV loads in salivary glands, the endpoint of infection. This is in contrast with strong positive correlations between DENV loads in a range of tissues and salivary gland loads for Wildtype mosquitoes. Lastly, there was no evidence of a heightened role for tissues with known immune function including the fat body and the Malpighian tubules in Wolbachia’s limitation of DENV. CONCLUSION/SIGNIFICANCE: We conclude that the efficacy of DENV blocking in Wolbachia infected mosquitoes is not reliant on any particular tissue. This work therefore suggests that the mechanism of Wolbachia-based antiviral effects is either systemic or acts locally via processes that are fundamental to diverse cell types. We further conclude that the relationship between DENV blocking and Wolbachia density is not linear in mosquito tissues